Peltojen etäisyyden vaikutuksesta viljelmän kannattavuuteen - Suomela, Samuli (Agricultural and Food Science, 1947)
The purpose of this study is briefly to examine the influence that the distance to the fields has on the profitableness on 91 farms of size class III (from 25 to 50 of converted field), wich during 1934 —1939 were reviewed by the Board of Agriculture. The farms are grouped, according to the average distance to the fields, in 3 groups: A, average distance under 600 meters; B, average distance from 600 to 1 000 m. and C, average distance over 1 000 m. Further they are grouped according to size into group I from 25 to 37,5 converted field hectares and group II from 37,5 to 50 converted field hectares. The research shows that the net profit and percentage of profitableness diminish considerably when the average distance to the fields increases (tables 4 and 5) and that the decrease is much steeper in connection with changes in small distance groups than with respect to similar changes in higher distance brackets. But the expenditure of work, on the other side, does not notably increase and the management costs do in fact diminish when the distance increases. This is a result of a considerable lowering in the intensity of the field and the overall cultivation of the farm as the location of the fields becomes less favourable. The diminution of the net profit is a consequence of the decrease in total yields. The earlier method of taking the loss of time caused by the location of fields into calculations on different crops and to make the deductions as to the influence of the distance to the fields on the profitableness of farming directly from these calculations, is therefore not in harmony with practical facts.